The role of reinsurance in increasing returns and reducing risks for insurance companies: An empirical study in the National and Iraqi Insurance Companies (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The current research aims to verify the nature of the relationship and impact between reinsurance and the return and risk of the insurance company. In order to test the hypotheses, data related to the research variables were collected from the financial department of the researched companies, relying on the inductive and deductive approach in analyzing information for the annual reports and financial statements of the National and Iraqi Insurance Company and the insurance portfolios for the period from 2019 to 2023, and using some financial analysis indicators to measure (reinsurance ratios, commission rates earned on reinsurance operations, and financial surplus rate). In order to obtain the results, a number of statistical methods were used in accordance with the nature of the collected data, as the Statistical Package for the Social Sciences (SPSS) program was used to calculate the statistical indicators. The research was applied to the National and Iraqi Insurance Company, which is one of the oldest government insurance companies in Iraq. The study concludes that there is a significant increase in the reinstatement rate index for some portfolios, such as the (engineering and marine) portfolio, as the National Insurance Company waives more than half of the collected premiums, which makes the insurance company a mere intermediary between the insured and the reinsurance companies, and which indicates that the company does not rely on a good risk selection policy to achieve the highest desired returns for it.